Regulation of Chemokine Activity – A Focus on the Role of Dipeptidyl Peptidase IV/CD26 - Metzemaekers, Mieke; Van Damme, Jo; Mortier, Anneleen; Proost, Paul (Frontiers in Immunology, 2016)
Chemokines are small, chemotactic proteins that play a crucial role in leukocyte migration and are therefore essential for proper functioning of the immune system. Chemokines exert their chemotactic effect by activation of chemokine receptors, which are G protein-coupled receptors (GPCRs), and interaction with glycosaminoglycans (GAGs). Furthermore, the exact chemokine function is modulated at the level of posttranslational modifications. Among the different types of posttranslational modifications that were found to occur in vitro and in vivo, i.e. proteolysis, citrullination, glycosylation and nitration, NH2-terminal proteolysis of chemokines has been described most intensively. Since the NH2-terminal chemokine domain mediates receptor interaction, NH2-terminal modification by limited proteolysis or amino acid side chain modification can drastically affect their biological activity. An enzyme that has been shown to provoke NH2-terminal proteolysis of various chemokines is dipeptidyl peptidase IV or CD26. This multifunctional protein is a serine protease that preferably cleaves dipeptides from the NH2-terminal region of peptides and proteins with a proline or alanine residue in the penultimate position. Various chemokines possess such a proline or alanine residue and CD26-truncated forms of these chemokines have been identified in cell culture supernatant as well as in body fluids. The effects of CD26-mediated proteolysis in the context of chemokines turned out to be highly complex. Depending on the chemokine ligand, loss of these two NH2-terminal amino acids can result in either an increased or a decreased biological activity, enhanced receptor specificity, inactivation of the chemokine ligand or generation of receptor antagonists. Since chemokines direct leukocyte migration in homeostatic as well as pathophysiologic conditions, CD26-mediated proteolytic processing of these chemotactic proteins may have significant consequences for appropriate functioning of the immune system. After introducing the chemokine family together with the GPCRs and GAGs, as main interaction partners of chemokines, and discussing the different forms of posttranslational modifications, this review will focus on the intriguing relationship of chemokines with the serine protease CD26.